Simultaneous multiple responses modelling, optimization and correlations of Asian type peanuts (Arachis hypogaea L.) roasting using response surface methodology - Mohd Rozalli, Norazatul Hanim; Chin, Nyuk Ling; Yusof, Yus Aniza (Akademiai Kiado, 2014)
The effect of hot-air roasting temperatures and time on colour (L*), moisture content (% d.b.), hardness (N), and fracturability (mm) attributes of two different type of peanuts (China and India origin) were investigated using response surface methodology (RSM). The central composite design (CCD) was used to investigate temperatures ranging from 130–170 °C (China) and 130–200 °C (India), while roasting time was from 20–80 min (China) and 15–50 min (India). The results revealed that temperature and time have significant effect on all the responses. Increase in roasting time and temperature caused a decrease in all the responses for both peanuts. A feasible experimental condition of peanut roasting obtained from the optimisation of simultaneous multiple attributes’ response for the China and India peanuts was 152 °C for 60 min and 158 °C for 45 min, respectively. The strongest linearrelationship was found between hardness and fracturability, while the weakest was between colour and fracturability for both peanuts.